MODEL KOOPERATIF DENGAN BANTUAN MM DALAM PEMBELAJARAN IPA DI PROGRAM STUDI PGSD - Yeni Puji Astuti (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
In the era of industrial revolution 4.0, science learning in Higher Education especially in Elementary School Teacher Education Study Programs must be actively applied, in order to produce graduates who have high abilities and skills. One way is to apply a cooperative learning model assisted by the Student Module (MM). This learning model is suitable to be applied in Higher Education because it prioritizes group work, besides it can train student skills in expressing opinions from the results of group discussions. With the help of MM, students can do assignments in more structured lectures, so that material with a broad scope can be completed thoroughly and on time